Design test fixture for high cycle fatigue on polymer mixed concrete / Rosliezan Md Husain and Yusnizam Abd Jalil - Md Husain, Rosliezan; Abd Jalil, Yusnizam (2004)
Fixture is defined as a production tool that locates, holds and supports the work or specimen securely, so the required processing can be performed successfully. Therefore fixture is one of the important component parts as far as such process is concerned. High cycle fatigue is fatigue that occurs at relatively large numbers of cycle and in caused by high frequency vibrations in both static and rotating hardware. The distinction between high cycle fatigue and low cycle fatigue is made by determining whether the dominant component of the strain imposed during cyclic loading is elastic (high cycle) or plastic (low cycle), which in turn depends on the properties of the material and on the magnitude of the stress. The main objectives in this research are to design and fabricated the test fixture to perform high frequency fatigue test on compact tension and 3 point bend specimen configuration and to study the fatigue crack growth rate of Polymer Mixed Concrete due to high frequency fatigue. From this work, the both of test fixture were successfully built that provide rigidity and reliability. Initial investigation on the effect of high frequency fatigue load on Polymer Mixed Concrete was also conducted.